Ontogenetic instars of the oribatid mite Spatiodamaeus kalugaensis sp. nov. (Acari, Oribatida, Damaeidae) from Russia - Ermilov, Sergey G.; Miko, Ladislav; Kolesnikov, Vasiliy B.; Salavatulin, Vladimir M. (Zootaxa, 2023)
A new species of the genus Spatiodamaeus (Oribatida, Damaeidae) is described from Russia, based on adult and juvenile instars collected from bark of Acer platanoides and soil-litter of mixed and broadleaf forests in European part of Russia and Western Siberia. The adult of Spatiodamaeus kalugaensis sp. nov. is similar to S. nortoni (Bayartogtokh, 2004) comb. nov. in having epimeral neotrichy but differs from the latter by the presence of the parastigmatic tubercle Sa, the form of the parastigmatic tubercle Sp and the notogastral setae c1, c2, and the barbulation of the rostral, epimeral, anogenital, and notogastral setae of p-series. Comparisons between juvenile instars of the new species and the known juveniles of Spatiodamaeus and Epidamaeus are presented.